Black cumin seed oil, protein, concentrates, and hydrolysate - Elnour, Ahmed A M; Mirghani, Mohamed Elwathig Saeed; Elfadil, Abdelgadir A.; Sallam, El Bashier; Bani, Ibrahim (Academic Press of ELSEVIER, 2023)
Medicinal plants (MPs) have prevented and cured diseases for many centuries by using different indigenous ecosystems in medicine and folk medicines (FMs). Furthermore, MPs are also used to prepare herbal medicines (HMs) as they are considered safe compared to contemporary allopathic drugs. Many researchers concentrate on MPs, since only inadequate plant types have been studied systematically. They have examined their therapeutic activities, potential, safety evaluation, toxicological studies, and mechanism of action. So, considering the medicinal value and its therapeutic potential, it would spotlight the biological activities of black cumin seed oil (BCSO). Among several MPs, the black seed (also known as black cumin) (Habat-ul-Sauda), since numerous types of research have revealed its broad spectrum of pharmacological potential (Family Ranunculaceae), is emerging as a phenomenon herb with a rich history and religious background. Black cumin seed (BCS), Nigella sativa, is a plant native to North Africa, Southwest Asia, and Southern Europe. It is grown in many countries worldwide, including South Europe, Syria, Turkey, Saudi Arabia, the Middle East Mediterranean region, India, Pakistan, and Afghanistan. Thus, the black seed is economically available worldwide. BCSO is widely used as an alternative medication. Many beneficial substances are generated directly from BCSO, whereas others are chemically altered natural products. This study confirmed the use of BCSO in nutritional, pharmaceutical, and medical sectors and some bioactive elements found in their oil and by-products, including AAs, FAs, and the TQ. Further research is required to understand BCSO activity, its bioactive components, and its nutritional impact. Modifying the molecular structure of alphahederin, TQ, and other BCSO bioactive compounds may lead to more effective and safe treatments in the future. To combat resistance issues, BCSO and its bioactive compounds such as alpha-hederin, TQ, and others can be used in appropriate combinations with existing chemotherapy drugs. Researchers should also investigate TQ’s molecular and cellular targets. This book chapter is dedicated to all scientists who wish to do more preclinical and clinical research on using BCSO to treat various communicable illnesses.